Research on the positioning of buried polyethylene pipelines considering the acoustic attenuation characteristics - Ao Zhang; Disheng Zhong; Zhuo Xu; Hanyu Zhang (Scientific Reports)
Abstract Polyethylene pipelines have been widely used in the construction of urban pipelines. Due to the non-magnetic and non-conductive properties of polyethylene pipelines, traditional metal pipe positioning techniques are unable to effectively detect polyethylene pipelines. To improve the positioning accuracy of polyethylene pipelines, this paper proposes a pipeline positioning method considering the attenuation characteristics of acoustic wave. The proposed method combines active acoustic positioning technology with the resonance characteristics of pipelines, which can accurately locate the horizontal position and depth of pipelines simultaneously. Firstly, based on the theory of acoustic wave attenuation, the solution of the acoustic wave equation in non-ideal media is derived. Then, the amplitude attenuation characteristics of acoustic waves in a buried polyethylene pipeline are analyzed using finite element simulation. By observing the maximum amplitude of acoustic signals, the horizontal direction of buried polyethylene pipelines can be effectively determined. To determine the depth of buried pipelines, the resonance phenomenon is utilized and the attenuation of acoustic waves is considered to obtain the mathematical model. The largest error of simulation results is 2% for horizontal direction, and 7.8% for depth position, indicating the proposed method can effectively locate the buried pipeline. Finally, a complete pipeline excitation and data acquisition system is established through an on-site experiment, and the experiments are conducted under various burial depth conditions. The experimental results show that the horizontal positioning error and depth positioning error are both less than 8%, indicating the proposed method can accurately locate the buried pipeline.